Relationship between Gravidity and Low Birth Weight in Kendari City Hospital - Lisnawati; Tawakkal; Ira Nurmala; Fajar Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between gravity and the incidence of low birth weight in Kendari city hospital. This research method is quantitative, the sample of this research is 58 respondents. Research results It is known from the results of data analysis that the chi-square test value is obtained, namely the calculated X2 value is 10,434 or greater than the X2 table with a value of 3,841, and it is known that the P value is not greater than Alpha (0.005 <0.05). This can be interpreted that the independent variable meme is related the dependent variable with the closeness of the variable relationship can be seen from the Phi value, which is 0.424 which lies in the range of the coefficient interval 0.40-0.599 which can be concluded that there is a relationship with a moderate level. It is recommended to provide more Health Education for pregnant women as an early detection of the risk of LBW